The response of Pinus caribaea mor. var. Hondurensis seedlings to nitrogen, phosphorous and potassium fertilizers - Srivastava, P.B.L.; Naruddin, Abang; Zainorin, B.Abang (Martinus Nijhoff, The Hague/Kluwer Academic Publishers, 1979)
A soil pot culture experiment was conducted to study the response of Pinus caribaea var. hondurensis seedlings to the N, P, K fertilizers in a 33 factorial combination of nutrients in four replicates. For this purpose, seedlings were grown in plastic pots in soils collected from Bahau pine experimental area. These soils belong to Durian series and are generally poor in nutrients. The seedlings were supplied with 112 kg/ha, 336 kg/ha and 560 kg/ha (100 lb/ac, 300 lb/ac and 500 lb/ac) of N, P, K in solution form in all possible combinations. Periodic growth measurements were taken and dry matter production was estimated at the conclusion of the experiment. The results indicate that phosphorous is the most important nutrient for the height growth of seedlings. The absolute height increment under the best treatment combination (N1P3K1) was about threefolds (25.7cm) compared to 8.8 cm in the control. It was also found that higher levels of N and K, though not beneficial to height growth, resulted in better radial growth and more dry matter production compared to control plants. However, highest levels of N and K in the present experiment produced inhibitory influence as regards height growth even in the presence of low level of phosphorous. The study indicates that application of phosphorous at least at the rate of 560 kg/ha per plant is necessary on this type of soil to boost the initial height growth of Pinus caribaea var. hondurensis. Nitrogen at the rate of 336 kg/ha and potassium at the rate of 112 kg/ha will induce better radial growth.